Quantitative analysis of polyphenolic compounds in two different cultivars of marigold (Tagetes erecta L.) using high-performance thin-layer chromatography - Mir, Rayees Ahmad; Irshad, Saba; Argal, Surendra; Agarwal, Rajiv Mohan; Khatoon, Sayyada (Frontiers in Horticulture, 2023)
Marigold (Tagetes erecta L.), a popular ornamental plant of the family Asteraceae, is commonly cultivated in many countries, including India, for its decorative flowers. The plants grow easily in a variety of soil and climatic conditions and have been reported to damage the nematode population of soil and control indirectly harmful microbes. High-performance thin-layer chromatography (HPTLC) was utilized in the present study, with a view to identify some important biologically active compounds in the flowers and leaves of two cultivars of marigold, Pusa Narangi Gainda (PNG) and Pusa Basanti Gainda (PBG). Quantitative analyses were carried out using silica gel thin-layer chromatography (TLC) plates and toluene–ethyl acetate–formic acid (T-E-F) (13:11:2 v/v/v) as the mobile phase used. Bands of gallic acid, caffeic acid, quercetin, p-coumaric acid, and kaempferol were observed. The results revealed a greater number of compounds in leaves than in flowers, and that the cultivar PNG accumulated a greater number of compounds than PBG. Gallic acid was found in leaves and flowers of both cultivars; however, it was found maximum in the flowers of cultivar PBG. Caffeic acid and quercetin were detected in the leaves of both cultivars, whereas p-coumaric acid was detected only in the leaves and kaempferol only in the flowers of cultivar PNG. The information generated in this report may be meaningfully used for the furtherance of research on marigolds as a natural source of antioxidants, insecticides, herbicides, etc.